Multi-biometric template protection based on Homomorphic Encryption. (July 2017) - Gomez-Barrero, Marta; Maiorana, Emanuele; Galbally, Javier; Campisi, Patrizio; Fierrez, Julian
Highlights: New framework for multi-biometric template protection based on Homomorphic Encryption. Thorough eval of compliance with ISO/IEC IS 24745 on biometric information protection. Detailed complexity overhead analysis. Abstract: In spite of the advantages of biometrics as an identity verification technology, some concerns have been raised due to the high sensitivity of biometric data: any information leakage poses a severe privacy threat. To solve those issues only protected templates should be stored or exchanged for recognition purposes. In order to improve the performance and achieve more secure and privacy-preserving systems, we propose a general framework for multi-biometric template protection based on homomorphic probabilistic encryption, where only encrypted data is handled. Three fusion levels are thoroughly analysed, showing that all requirements described in the ISO/IEC 24745 standard on biometric data protection are met with no accuracy degradation. Furthermore, even if all the process is carried out in the encrypted domain, no encryptions are necessary during verification, thereby allowing an efficient verification which can be deployed for real-time applications. Finally, experiments are carried out on a reproducible research framework. The results obtained show high accuracy rates, reaching EERs as low as 0.12%, and requiring protected templates comprising 200 KB.